Gambaran Tingkat Kepatuhan Pengobatan Pasien TB Paru: Overview of Treatment Adherence Level of Pulmonary TB Patients - Endang Martini; Rika Sarfika; Siti Yuliharni (NERS Jurnal Keperawatan, 2024)
Adherence to tuberculosis (TB) treatment is crucial for achieving cure and preventing drug resistance. Low adherence can lead to treatment failure and increase the risk of infection transmission. Therefore, assessing medication adherence in TB patients is necessary to determine the extent to which patients follow prescribed treatment regimens. This study aims to identify the level of medication adherence among pulmonary TB patients in Kota Lahat. A descriptive analytic design was used in this study. The population consisted of pulmonary TB patients undergoing treatment at five public health centers (PHC) in Lahat City between July 26 and August 5, 2024. A non-probability total sampling technique was employed. Medication adherence was measured using the Morisky Medication Adherence Scale (MMAS-8). Of the total respondents, 51% showed low adherence, 29% moderate adherence, and 20% high adherence. Demographic characteristics revealed that the majority of respondents were male (64.7%), with the largest age group being pre-elderly (42.7%). Most respondents had a bachelor's degree (40.7%) and were employed (70.7%). More than half of the respondents (63.3%) were smokers, with a smoking history of ≥10 years. The level of medication adherence among pulmonary TB patients remains low. Collaborative efforts are needed to enhance education and support for patients to improve adherence, thereby increasing treatment success.